2016
DOI: 10.1080/00288233.2016.1188831
|View full text |Cite
|
Sign up to set email alerts
|

Effects of including forage herbs in grass–legume mixtures on persistence of intensively managed pastures sampled across three age categories and five regions

Abstract: (2016) Effects of including forage herbs in grass-legume mixtures on persistence of intensively managed pastures sampled across three age categories and five regions,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…In summary, while the results reported are from just one sampling date, they show that small diverse patches within pasture do have a significant impact on the abundance and species richness of the parasitoids that aggregate on them. Given the positive benefits of the inclusion of chicory and/or plantain in New Zealand pastures on predator and parasitoid abundance (Tozer et al 2016), more detailed study is warranted to quantify how pasture plant diversity impacts on pasture ecosystem stability and pest outbreak risk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In summary, while the results reported are from just one sampling date, they show that small diverse patches within pasture do have a significant impact on the abundance and species richness of the parasitoids that aggregate on them. Given the positive benefits of the inclusion of chicory and/or plantain in New Zealand pastures on predator and parasitoid abundance (Tozer et al 2016), more detailed study is warranted to quantify how pasture plant diversity impacts on pasture ecosystem stability and pest outbreak risk.…”
Section: Discussionmentioning
confidence: 99%
“…Poor pasture persistence is ranked as one of the most important factors currently limiting farm economic performance in New Zealand, with drought and insect pests implicated as the main drivers (Tozer et al 2016). However, there is limited research on terrestrial biodiversity in production landscapes and how it may impact on agroecosystem communities and resilience (Moller et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of P. lanceolata and C. intybus of increased productivity during summer months [58] and the tolerance of hot and dry conditions over other common species [59] are desired features that farmers need in order to extend the grazing period, helping to increase the persistence of sown species and reducing weed ingress when forage herbs are included in the pasture mixture on sheep and beef systems [60] and increasing milk production as a part of multispecies swards [61]. The forage herb C. intybus is suggested as a potential alternative to F. arundinacea, D. glomerata and L. perenne under frequent heat and drought stress [62].…”
Section: Overview Of the Genus And Species Importedmentioning
confidence: 99%
“…Sanderson et al [97] reported that the inclusion of diverse forage species in grass-legume mixtures reduced weed ingress simply because the greater herbage mass prevented weed invasion. Also, Tozer et al [98] stated that the addition of forage herbs, Cichorium intybus L. or Plantago lanceolate L., in grass-legume mixtures reduced weed infestations in sheep and beef farms.…”
Section: Agronomic Tactics For Pasture Weed Controlmentioning
confidence: 99%